Facing the hospitalization of the adult patient by the caregiver family member - Caroline Passos Arruda; Giovana Calcagno Gomes; Manoela Cunha Nicoletti; Vanessa da Silva Tarouco; Cintia Camila Santos de Souza Costa; Aline Ney Grehs (Universidade Federal de Santa Maria, 2019)
Objective: to know how the caregiver family member faces the hospitalization of the adult patient. Method: descriptive and exploratory qualitative research conducted in April 2018 at a University Hospital in southern Brazil. A total of 20 caregiver family members participated in the study. Data were collected through interviews and subjected to Thematic Analysis. Results: The feelings presented regarding hospitalization were worry, anxiety, fear of death and tranquility. The family elected one of the family members to be the primary caregiver or took turns. Sometimes the caregiver needed to take time off to care of the patient, other family members dedicated themselves to aspects of living outside the hospital, and the family expanded. Final Considerations: It is important to direct care to the caregiver family member, contemplating humanization, bonding and communication, as he/she is the greatest ally of the health team members in the hospital.